2018
DOI: 10.4038/sljch.v47i4.8595
|View full text |Cite
|
Sign up to set email alerts
|

Building characteristics and sick building syndrome among primary school students

Abstract: Background: The sick building syndrome (SBS) describes situations in which building occupants experience acute negative physical and mental effects linked to the time spent in a contaminated area without any identified illness. Objective: The study was carried out in order to assess the prevalence of SBS among primary school students in Qom, Iran, and the association between SBS symptoms and personal, psychosocial and environmental factors.. Method: A descriptive-analytical study was conducted on 24 primary sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This study also found a higher prevalence of general symptoms among girls when compared to boys. A previous study based in Iran school also found more symptoms among female students [ 22 ], while another Japanese school children study reported more symptoms among boys [ 17 ]. On the other hand, studies among adult populations have reported higher SBS rates among women [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also found a higher prevalence of general symptoms among girls when compared to boys. A previous study based in Iran school also found more symptoms among female students [ 22 ], while another Japanese school children study reported more symptoms among boys [ 17 ]. On the other hand, studies among adult populations have reported higher SBS rates among women [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was carried out in Salafchegan city, a special economic zone, located in the central part of Qom province, Iran. Located in the central part of Iran, Qom is a province that's known for being the smallest in the country and having a semi-arid climate [28][29][30] . The area of the Salafchegan district is 55.4 km 2 31 .…”
Section: Selection Of Study Sitesmentioning
confidence: 99%
“…Qom (capital city of Qom province), one of the most populous cities in Iran, is located in the center of Iran with a semi-arid climate (6)(7)(8)(9). Historically, the water supply of Qom has been of great importance due to the arid environment of this city and water scarcity.…”
Section: Study Areamentioning
confidence: 99%